The Impact of China's Huawei Technology Development on Contestation Relations between United States-China in 2018-2021 - Dewi, Ida Ayu Utari Pradita; Suwecawangsa, Adi Putra; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 1 (2024): JURNAL DIKSHI, 2024)
This study aims to describe the contestation relations between United States and China in 2018-2021 related to the development of China's Huawei technology. The development of human civilization influences phenomena in international relations, especially relations between states. The era of the 4th industrial revolution made technology a vital power potential for the states. Most of the global giant technology companies originate from the United States, but nowadays China's technology industry led by Huawei is starting to excel globally. Therefore, there is contestation in the relationship between the United States and China. The data in this study were obtained through literature and documents such as Huawei's annual report and reports released by research institutes. In addition, the research also uses some conceptual framework such as technology as an element of power, security dilemmas, and game theory: tit for tat in conducting analysis. This research ultimately provides an answer that regardless of China's intention in developing its technology, Huawei's technological development poses a threat or a sense of insecurity for the United States. This creates a security dilemma for the United States which in turn leads to pre-emptive action. The United States' pre-emptive action against Huawei drew a retaliatory response from China. China implemented a tit for tat strategy as a step to retaliate the actions of the United States. The interaction action by both states has created a contestation in the relationship between the United States and China because of Huawei's technological developments.